Hubungan pengetahuan early sex education (ese) dengan perilaku seks pranikah pada remaja awal di Desa Cibadak Kecamatan cikupa Kabupaten Tangerang 2023 - Dewi Habsari, Pratika (Yayasan Pusat Pendidikan Vanchapo, 2023)
Puberty affects some teenagers more strongly than others and influences some behaviors more strongly than others. Body image, interest in dating and sexual behavior are influenced by changes during puberty. The aim of this research was to determine the relationship between knowledge of teenagers about sex education and behavior that leads to free sex in Cibadak Village, Cikupa District. The population in this study was 30 respondents, using a proportional random sampling technique. Data analysis uses multiple linear regression. The instrument used is a questionnaire. The results of the analysis from multiple linear regression are Y = 3.501 - 0.297X1 - 0.309X2 so that from this research the R2 coefficient of determination value is 0.615. With a p value = 0.000, which means the significance value is <0.05, which means there is a relationship between knowledge, attitudes of teenagers regarding sex education and behavior that leads to free sex. The conclusion from this research is that there is a significant relationship between knowledge and attitudes of teenagers regarding sex education and behavior that leads to free sex in Cibadak Village, Cikupa District. Suggestions from researchers for Cibadak Village, Cikupa District, are for parents and villages to increase their role as counselors for teenagers who have problems regarding reproductive health, especially regarding sex and teenage sexual behavior.